EFEKTIVITAS MEDIA VLOG BERBAHASA JEPANG TERHADAP KEMAMPUAN POLA KALIMAT DALAM PENULISAN SAKUBUN (KARANGAN) - Utari, Retno (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2020)
This research is entitled "The Effectiveness of Japanese Language Vlog Media Against the Ability of Sentence Patterns in Sakubun Writing (Essays)". (Quantitative Approach in 3rd Semester Students of the Japanese Language Education Study Program FKIP UHAMKA Jakarta Academic Year 2019-2020). In this millennial era, everyone has the right to express his ideas through in various media. One of these media is a Japanese-language Vlog which contains learning in the field of Japanese Language Education, such as Jerome Polin with his channel named Nihon go Mantappu. There is also another channel called Belajar Bahasa Jepang, and WaGoMu. They all carry the theme of learning Japanese online. This research aims to determine whether or not there is an influence of the use of Japanese Language Vlog Media on the Ability of Sentence Patterns in Sakubun Writing (Essays) for 3rd Semester students in the Japanese Language Education Study Program FKIP UHAMKA. This research uses quasi-experimental methods. The sample and data source of this research were 20 students in 3rd Semester of Japanese Language Education Study Program FKIP UHAMKA, while the data source was the result of student essays. Based on calculations using the SPSS program, from the results of pre-test are obtained a range or distance between the smallest value and the largest value of 38, a minimum value of 50, a maximum value of 88, an average value of 75, and from the Post-test results obtained a range or distance value between the smallest value and the largest value of 30, a minimum value of 65, a maximum value of 95, an average value of 80.4. Based on the SPSS calculation results obtained a sig value of 0.058> 0.005, this means reject H0 or accept H1 which means there is a difference between learning before using vlog media with learning after using vlog media. It can be said that Japanese Language Vlog Media is effective in improving sentence pattern abilities in Sakubun learning. The results of the Questionnaire stated that Japanese Language Vlog Media is very interesting, enthusiastic and can improve the ability of Japanese Sentence Patterns in Sakubun Writing (Essays)